Adult Camk2a gene reinstatement restores the learning and plasticity deficits of Camk2a knockout mice - Pomme M.F. Rigter; Ilse Wallaard; Mehrnoush Aghadavoud Jolfaei; Jenina Kingma; Laura Post; Minetta Elgersma; Ype Elgersma; Geeske M. van Woerden (iScience, 2022)
Summary: With the recent findings that mutations in the gene encoding the α-subunit of calcium/calmodulin-dependent protein kinase II (CAMK2A) causes a neurodevelopmental disorder (NDD), it is of great therapeutic relevance to know if there exists a critical developmental time window in which CAMK2A needs to be expressed for normal brain development, or whether expression of the protein at later stages is still beneficial to restore normal functioning. To answer this question, we generated an inducible Camk2a mouse model, which allows us to express CAMK2A at any desired time. Here, we show that adult expression of CAMK2A rescues the behavioral and electrophysiological phenotypes seen in the Camk2a knock-out mice, including spatial and conditional learning and synaptic plasticity. These results suggest that CAMK2A does not play a critical irreversible role in neurodevelopment, which is of importance for future therapies to treat CAMK2A-dependent disorders.